Using Garden-Based Service-Learning to Work Toward Food Justice, Better Educate Students, and Strengthen Campus-Community Ties - David Aftandilian; Lyn Dart (The University of Alabama, 2022)
In this article, we present several approaches for using garden-based service-learning to work toward food justice, better educate undergraduate students, and strengthen campus-community ties. We begin by introducing several key concepts related to food justice, community gardens as a strategy for strengthening food security and community development, and service-learning as a pedagogical tool for educating students about social justice, civic engagement, and personal responsibility for positive social change. We then discuss three of our service-learning projects in depth from an interdisciplinary perspective: the Fairmount Community Garden, the North Side Garden Survey, and the Como Community Garden. We evaluate the success of our approaches using multiple measures and identify the benefits our approaches have provided for undergraduates, community partners, communities served by the gardens, educators, and our university. We also discuss lessons we have learned, offer suggestions for best practices to follow in developing future garden-based service-learning projects, and compare and contrast our pedagogy with that of critical service-learning.